Dynamics of globalization location-specific advantages or liabilities of foreignness? - Asmussen, Christian Geisler (Emerald, 2011)
Cross-border flows of goods, services, capital, knowledge, and ideas have substantially increased over the last decades. These developments have increased the interdependencies among previously separated economies, given rise to arguments regarding the flattening of the world. Yet, firms investing overseas continue to experience substantial liabilities stemming from their foreignness. At the same time new locations are appearing on the global map that offers very attractive location-specific advantages. In addition, the range of participants in international competition has widened, in terms of both the number of countries involved and the types of firms competing, to encompass developed market firms expanding beyond industrialized countries, and emerging market firms joining global competition. The focus of this volume is on how the interface between firm-specific advantages, liability of foreignness, and location-specific advantages are spelled out in the more global world.
Keywords: Business & Economics -- International -- General.; Political Science -- Globalization.; Business & Economics -- General.; International business.; Globalization.; elektronické knihy; electronic books